2010
DOI: 10.1111/j.1467-8659.2009.01546.x
|View full text |Cite
|
Sign up to set email alerts
|

Time‐Dependent 2‐D Vector Field Topology: An Approach Inspired by Lagrangian Coherent Structures

Abstract: This paper presents an approach to a time-dependent variant of the concept of vector field topology for 2-D vector fields. Vector field topology is defined for steady vector fields and aims at discriminating the domain of a vector field into regions of qualitatively different behaviour. The presented approach represents a generalization for saddle-type critical points and their separatrices to unsteady vector fields based on generalized streak lines, with the classical vector field topology as its special case… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 24 publications
1
50
0
Order By: Relevance
“…In contrast, time lines crossing forward LCS and integrated in forward direction are subject to strong deformation (due to separation and/or shear). At the same time, Sadlo and Weiskopf [SW10] have shown that time lines seeded exactly on a saddle‐type LCS collapse to a single point. For the same reason, backward time lines have to align with dominant forward LCS structures in this case: If the (collapsed) saddle line is enclosed by time lines at time step t 0 , the same time lines have to enclose this structure at any other time step t0τ, since both structures are guaranteed to be material structures, i.e.…”
Section: Materials Line Advection In 2d Flow Fieldsmentioning
confidence: 92%
See 1 more Smart Citation
“…In contrast, time lines crossing forward LCS and integrated in forward direction are subject to strong deformation (due to separation and/or shear). At the same time, Sadlo and Weiskopf [SW10] have shown that time lines seeded exactly on a saddle‐type LCS collapse to a single point. For the same reason, backward time lines have to align with dominant forward LCS structures in this case: If the (collapsed) saddle line is enclosed by time lines at time step t 0 , the same time lines have to enclose this structure at any other time step t0τ, since both structures are guaranteed to be material structures, i.e.…”
Section: Materials Line Advection In 2d Flow Fieldsmentioning
confidence: 92%
“…In literature, the relation of streak lines (and streak surfaces) to LCS has been discussed in detail by Sadlo et al . [SW10] and Üffinger et al . [USE12].…”
Section: Materials Line Advection In 2d Flow Fieldsmentioning
confidence: 95%
“…Sadlo and Weiskopf [SW10] present an approach to time‐dependent 2D VFT based on generalized streak lines , i.e., streak lines with a moving instead of a fixed seed point. This allows them to give a generalized definition of saddle‐type critical points for unsteady flow.…”
Section: Classical Vector Field Topologymentioning
confidence: 99%
“…Shadden et al [SLM05] have shown that ridges of FTLE are approximate material structures, i.e., they converge to material structures for increasing integration times. This fact was used in [SW10] to extract topology‐like structures and in [LM10] to accelerate the FTLE computation in 2D flows. Also in the visualization community, different approaches have been proposed to increase performance, accuracy and usefulness of FTLE as a visualization tool [SP09, GLT*09, GGTH07, SP07, SRP11, KPH*09].…”
Section: Related Workmentioning
confidence: 99%